Sharia Banking Contribution To Financial Deeping In Supporting Indonesia Economic Recovery - Sandi Mulyadi; Asep Suryanto (UIN Siber Syekh Nurjati Cirebon, 2022)
The background of the research is the issue of research on Indonesia's financial deepening condition during the pandemic to describe the condition of Islamic banking on financial deepening in Indonesia before and during the pandemic, using the variables of total assets, third party funds, and Islamic banking financing. The method used in this research is descriptive quantitative by analyzing secondary data which is processed using Eviews with the VECM method and using quarterly time series data from 2005-2021 with a total sample of 272 from all research variables.The results of data processing using VECM show several findings, namely: Assets have a long-term positive effect on financial deepening, and based on the IRF and FEVD financial deepening tests show a positive response to shock with a contribution of 77%. Meanwhile, TPF and Islamic bank financing have a long-term negative impact on financial deepening and based on the IRF and FEVD financial deepening tests, they showed a negative response to the shock of TPF with a contribution of 9% and showed a positive response to the financing shock with a contribution of 3%. Meanwhile, based on testing using IRF, the movement of financial deepening in response to shocks in these variables shows that it is stable in the future.Keywords: Financial Deepening, Islamic Banking, VECM Method